2019
DOI: 10.1111/pcn.12956
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double‐blind, placebo‐controlled study to assess the efficacy and safety of vortioxetine in Japanese patients with major depressive disorder

Abstract: Aim The burden of major depressive disorder (MDD) in Japan is high. This study aimed to evaluate the efficacy and safety of the multimodal antidepressant vortioxetine in Japanese patients with MDD. Methods Japanese patients aged 20–75 years with recurrent MDD and a Montgomery–Åsberg Depression Rating Scale (MADRS) score ≥ 26 were randomized to vortioxetine 10 or 20 mg or placebo in a phase‐3, double‐blind, 8‐week study. The primary end‐point was change in MADRS total score from baseline. Secondary end‐points i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 37 publications
6
47
0
Order By: Relevance
“…Pooled data were analyzed from the six short-term (8-week), randomized, double-blind, placebo-controlled, fixed-dose studies conducted by Takeda/Lundbeck that included vortioxetine 20 mg/ day for the treatment of MDD. [10][11][12][13][14][15] Patients randomized to vortioxetine 20 mg/day received vortioxetine 10 mg/day for the first week, and then 20 mg/day for the remaining 7 weeks of the study period. In all studies, efficacy was assessed using the MADRS as a primary endpoint.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pooled data were analyzed from the six short-term (8-week), randomized, double-blind, placebo-controlled, fixed-dose studies conducted by Takeda/Lundbeck that included vortioxetine 20 mg/ day for the treatment of MDD. [10][11][12][13][14][15] Patients randomized to vortioxetine 20 mg/day received vortioxetine 10 mg/day for the first week, and then 20 mg/day for the remaining 7 weeks of the study period. In all studies, efficacy was assessed using the MADRS as a primary endpoint.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Meta-Analysis of the Change from Baseline to Week 8 in MADRS Total Score Difference vs Placebo (Full Analysis Set, MMRM) in Fixed-Dose Studies[10][11][12][13][14][15] …”
mentioning
confidence: 99%
“… 11 In a more recent phase 3 randomized controlled trial enrolling Japanese patients with MDD (CCT-004), a significant improvement from baseline in the Montgomery–Åsberg Depression Rating Scale (MADRS) total score was demonstrated at weeks 6 and 8 with vortioxetine 20 mg and at week 8 with vortioxetine 10 mg, each compared with placebo ( P <0.05 for both doses). 12 …”
Section: Introductionmentioning
confidence: 99%
“…The results of the first two studies (35,36) investigating the effectiveness of vortioxetine for MDD in Japanese patients may have been due to a type II error (i.e., low statistical strength). These two studies (35,36) showed a greater placebo response and a similar drug response when compared with the Inoue et al (37)…”
Section: Efficacy and Tolerability -Short-term Clinical Trialsmentioning
confidence: 74%
“…In another recent eightweek phase III study, patients were randomized to dosage groups of 10 mg (n=165) or 20 mg (n=163) vortioxetine or a placebo (n=161). The findings indicated that vortioxetine at both 10 mg/day and 20 mg/day doses demonstrated strong antidepressant efficacy in Japanese patients with MDD and was well tolerated (37). Kishi et al (38) also conducted a systematic review and meta-analysis to investigate the benefits and effectiveness of vortioxetine in Japanese patients with MDD due to the different results seen in these phase III studies.…”
Section: Efficacy and Tolerability -Short-term Clinical Trialsmentioning
confidence: 99%